Experimental results of superconducting magnet behaviour during discharging into the external load - Ladislav Grega (Acta Montanistica Slovaca, 2008)
The basic part of every SMES (Superconducting magnetic energy storage) system is a superconducting magnet. All eventsof electrical nature which happen during its charging,, bypassing and discharging are transient. The article deals with experimentalresults of the superconducting magnet behaviour, especially during the period of its discharging into the prepared external load.